Changes in Allergy Symptoms and Depression Scores Are Positively Correlated In Patients With Recurrent Mood Disorders Exposed to Seasonal Peaks in Aeroallergens. (2007) - Postolache, Teodor T.; Lapidus, Manana; Sander, Evan R.; Langenberg, Patricia; Hamilton, Robert G.; Soriano, Joseph J.; McDonald, Jessica S.; Furst, Nancy; Bai, Jie; Scrandis, Debra A.; Cabassa, Johanna A.; Stiller, John W.; et al.
Abstract : Although growing evidence supports an association between allergy, allergens and depression, it remains unknown if this relationship is between "states" (possible triggers) or "traits" (possible vulnerabilities). We hypothesized that patients with recurrent mood disorders who are sensitized to tree pollen (as determined by allergen specific IgE antibodies), in comparison to those who are not sensitized, would report larger negative changes in mood during exposure to tree pollen in spring. We also hypothesized that differences between high and low tree pollen periods in self reported allergy symptoms would correlate positively with differences in self reported depression scores. We present 1-year preliminary data on the first 51 patients with unipolar or bipolar disorder (age: 19-63 years, 65% female, twelve patients were tree-pollen IgE positive). Ratings of mood and allergic disease status were performed once during the peak airborne pollen counts and once during the period of low airborne pollen counts, as reported by two local pollen counting stations. Linear regression models were developed to examine associations of changes in depression scores (dependent variable) with tree pollen sensitization, changes in the allergy symptom severity score, adjusted for gender and order of testing. We did not confirm the hypothesized relationship between a specific tree pollen sensitization and changes in mood during tree pollen exposure. We did confirm the hypothesized positive relationship between the changes in allergy symptoms and changes in subjects' depression scores (adjusted p<0.05). This result is consistent with previous epidemiological evidence connecting allergy with depression, as well as our recent reports of increased expression of cytokines in the prefrontal cortex in victims of suicide and in experimental animals sensitized and exposed to tree pollen. A relationship between changes in allergy symptom scores and changes in depression scores supports a state-level rather than only trait-level relationship, and thus lends optimism to future causality-testing interventional studies, which might then lead to novel preventative environmental interventions in mood disorders.